RELATIONSHIP OF PUPIL SIZE WITH REFRACTIVE ERROR IN METABOLIC SYNDROME AND NON METABOLIC SYNDROME: AMONG RURAL POPULATION IN MALANG - Holipah; AINI, KURROTUL; Sulistyowati, Anny; Vierlia, Wino Vrieda (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesNearly one in four Indonesians has metabolic syndrome (MS). One of the microvascular side effectsin Metabolic Syndrome affects the eyes. The aim of this study to evaluate the relationship of pupilsize with refractive error in MS and non-MS groups among rural populations in Malang. MethodsA descriptive study was carried out in 2019 in three villages in Malang districts. A detailed ocularexamination was conducted on all participants who attended a research facility. We definedpupillary abnormalities and clinically important refractive errors. Blood samples were obtained todetermine the parameter of the metabolic syndrome by IDF 2006 criteria. Subjects were classifiedinto 2 groups: Metabolic Syndrome status and non metabolic syndrome. Results953 participants completed the examination which consists of 944 right eyes and 942 left eyes. Theresults of visual acuity on the right eye: emmetropia in 434 eyes, myopia with 252 eyes, hyperopiawith 141 eyes, and astigmatism with 17 eyes where if it is not significant if associated with pupillaryabnormalities (P-value 0.893). On the left eye, the emmetropia results were 444 eyes, while formyopia were 244 eyes, hyperopia as many as 138, and astigmatism in 116 eyes and if associatedwith pupillary abnormalities, the result also not significant (P-value 0.864). The result of pupil sizewith metabolic syndrome 499 eye and non syndrome metabolic 454 eye are not significant (p-value0.649). ConclusionRefractive error didn’t relate pupil size in metabolic syndrome and non metabolic syndrome.